Repeated net-tDCS of the hypothalamus appetite-control network enhances inhibitory control and decreases sweet food intake in persons with overweight or obesity - Theresa Ester-Nacke; Ralf Veit; Julia Thomanek; Magdalena Book; Lukas Tamble; Marie Beermann; Dorina Löffler; Ricardo Salvador; Giulio Ruffini; Martin Heni; Andreas L. Birkenfeld; Christian Plewnia; et al. (Brain Stimulation)
Background: Reduced inhibitory control is associated with obesity and neuroimaging studies indicate that diminished prefrontal cortex activity influence eating behavior and metabolism. The hypothalamus regulates energy homeostasis and is functionally connected to cortical and subcortical regions especially the frontal areas. Objectives: We tested network-targeted transcranial direct current stimulation (net-tDCS) to influence the excitability of brain regions involved in appetite control. Methods: In a randomized, double-blind parallel group design, 44 adults with overweight or obesity (BMI 30.6 kg/m2, 52.3 % female) received active (anodal or cathodal) or sham 12-channel net-tDCS on the hypothalamus appetite-control network for 25 min on three consecutive days while performing a Stop-Signal-Task to measure response inhibition. Before and after stimulation, state questionnaires assessed changes in desire to eat and food craving. Directly after stimulation, participants received a breakfast buffet to evaluate ad-libitum food intake. An oral glucose tolerance test was conducted at follow-up. Resting-state functional MRI was obtained at baseline and follow-up. Results: The Stop-Signal Reaction Time (SSRT) was shorter in both active groups versus sham, indicating improved response inhibition. Additionally, a stronger increase in hypothalamic functional connectivity was associated with shorter SSRT. Caloric intake of sweet food was lower in the anodal group versus sham, but no main effects between groups were observed on total and macronutrient intake, food craving ratings and desire to eat. At follow-up, no differences were observed between groups on peripheral metabolism. Conclusion: Our study suggests that modulating hypothalamic functional network connectivity patterns via net-tDCS may improve food choice and inhibitory control.